Proyectos de integración en América Latina durante el siglo XX : el Mercosur y el sueño que continúa vigente (2010)
ABSTRACT: From the nineteenth century, with the formation of the national states in Latin America, have promoted an integrationist projects unfinished. Nowadays, the need of the integration is highlighted between countries in different aspects: economic, political, military man, diplomat. The first intention is to analyze historically the projects of integration in Latin America, and to give a look to the concept “Pan Americanism”, which arose in 1890 after the International American Conference: examining the “Pan Americanism” as concept and as politics that was closely linked to the emergence of The United States as world power, and the “Pan Americanism”, from the Latin-American position, understood as the effort on the part of the North American government for controlling politics and militarily to the different nations of the continent to promote its eventual economic expansion (Bobbio, Matteucci and Pasquino, 2002). The final intention is to emphasize the attempts of integration in the twentieth century, specially, from the projects appeared in the decade of sixty up to the formation of the Common Market of the South (Mercosur) in 1994. Likewise, to observe the difficulties that the regional community has had historically, and to analyze the experience of the Mercosur as the most serious Latin-American process of integration –in force in the beginning of the twenty-first century– in the economic area and, enclosedly, political.